Avaliação histológica da polpa dental de suínos após capeamento com Agregado Trióxido Mineral ou Hidróxido de Cálcio - Leites, Antonio Cesar Bortowiski Rosa (2006)
The main objectives of this study were to evaluate the use of the Sus scrofa domesticus swine in dental pulp experiments and analyze the histological pulp reaction to the direct application of mineral trioxide aggregate (MTA Angelus) and cement containing calcium hydroxide (Dycal). Class V cavities were prepared on incisors and pre-molar deciduous teeth of swine originated from crossbreed between Landrace and Large White of about 105 (±10 days) days old. Pulp exposures were obtained and after their homeostasis with saline, pulp capping was done with direct application of either MTA or Dycal. The animals were slaughtered after a period ranging within 7 and 70 days according to ISO 7405:1997. Four groups were created combining times and materials (HC_7d, HC_70d, MTA_7d and MTA_70d). The teeth were extracted and processed by HE histological technique; randomized cuts were examined under optical microscope with 100X enlargement by two different examiners. The criteria evaluated were: inflammatory response, tissue organization, reactive and reparative dentin being them all classified according to ISO 7405:1997 criteria. The Mann-Whitney Statistical test was used to compare both groups (α=5%). The MTA showed a tendency to accelerate the pulp healing process, being reparative dentin apposition initiated in the early stages of the healing process. Both materials showed similar pulp healing characteristics after 70 days. Despite higher levels of initial inflammation, specially related to Calcium Hydroxide (p<0.05), there was a remarkable formation of tertiary dentin after the period of 70 days, which shows the ability of swine dental pulp to respond to stimuli provoked by the materials used. The kind of animal used may give us an economically feasible model for further pulp response studies.